Occupational Hazards in Prosthodontic Practice: A Review - Ghimire, B (Journal of Nepalese Prosthodontic Society, 2020)
Every occupation has its own hazards and risks, prosthodontic practice is not an exception. With the evolution in materials and instrumentations, dental professionals have become prone to diverse risks of occupational hazards. These risks include exposure to physical and chemical agents, dental materials, infectious environment, inappropriate working pattern and psychosocial stress. The potential health risks of prosthodontic practice, use of dental materials and its impact in health have not been explored much. In this review, hazards and risks associated with prosthodontic practice have been highlighted and preventive measures to reduce the risks among professionals have been discussed.